Induction of DNA damage and cell death by Beta Amyloid Peptide and its modification by Tocotrienol Rich Fraction (TRF) - Musalmah; Rusdiah RJ; Noor Aini AH (Penerbit UKM, 2009)
Alzheimer’s disease (AD) is associated with increase neuron cell death and decline in cognitive function. This disease is characterized by plaque formation in the brain. It is believed that accumulation of beta amyloid peptide (Aβ) is an early sequence in the pathophysiology of AD. However, the mechanism of Aβ toxicity is unknown but may involve increase oxidative stress. This study was thus undertaken to determine the toxic effect of Aβ on DNA - an important biomolecule which is oxidized by free radicals, and cell apoptosis and its modulation by tocotrienol rich fraction (TRF). Neuroblastoma SH-SY5Y cell lines were treated either with 10μM Aß peptide; 5μg/ml TRF followed by 10μM Aß peptide or 10μM Aß peptide followed by 5μg/ml TRF. Untreated cells served as control. DNA damage was evaluated by the alkaline comet assay, cell viability by the 3-(4,5-dimetiltiazol-2-il)-5-(3-karboksimetoksifenil)2-(4-sulfofenil)-2H-tetrazolium (MTS) and the propidium iodide & calcein-AM staining to determine the number of viable and apoptotic cells. Results showed that Aß peptide induced a significantly higher DNA damage compared to control (p<0.05) and higher number of cell death. However treatment with TRF resulted in significantly less DNA damage, higher cell survival and decreased number of apoptotic cells as compared to Aß peptide treated cells (p<0.05,). Thus this study showed that Aß peptide causes DNA damage and ultimately cell death via apoptosis probably by inducing oxidative DNA damage. This is further supported by the fact that TRF is able to prevent the DNA damage and apoptosis.